Identification and semi-active control of structures with abrupt stiffness degradations. (15th January 2022) - Schleiter, Simon; Altay, Okyay
Abstract: This paper presents for variable stiffness tuned mass dampers (VS-TMDs) a vibration control algorithm combined with a nonlinear system identification method. The objective of the proposed approach is the control of multistory shear frame structures, which exhibit abrupt stiffness degradations. A stiffness variable control (SVC) algorithm is developed to control the stiffness of the VS-TMD, which is based on the mitigation of the potential energy of the structure. For the identification of the system parameters, an adaptive unscented Kalman filter (A-UKF) scheme is utilized. The paper describes the theoretical background of the proposed approach with its governing equations and conducts performance studies on a semi-actively controlled 2-story shear frame structure. Harmonic, white noise and earthquake excitation scenarios including seismic aftershock effects are investigated. Sensitivity studies are conducted. With the proposed approach, the abrupt stiffness changes of the structure are detected and the damper stiffness is adapted successfully. The results show that the SVC together with the A-UKF clearly outperforms the passive TMD control. Graphical abstract: Highlights: For the stiffness control of semi-active TMDs, a control algorithm is proposed. A potential energy based cost function is derived and minimized by gradient descent. The algorithm is coupled with an adaptive UKF for identification of abrupt changes. Harmonic, white noise and seismic excitation with aftershocks are investigated. A superior and robust control performance is observed.